Enfoque híbrido simulación-proceso analítico jerárquico: Caso de estudio del redise\~no de un restaurante - Caridad González Sánchez; Rosario Garza Ríos; Eduardo Pérez Malo (Revista de Métodos Cuantitativos para la Economía y la Empresa, 2014)
– The simulation has proved a particularly effective and powerful technique to evaluate different alternatives for solving problems, without being required actual experimentation. It is particularly useful for decision-making when you want to organize jobs in an organization where there are variables that have random behavior and influence the results. This paper proposes to use the discrete simulation for redesign and organization of work in a local food restaurant, which presents problems in its current design (among which are: delays in customer service, increased time waiting to sit), which has caused a decline in sales in the fourth quarter. With the simulation, it is obtained the modeling and evaluation of different alternatives of work organization and later, for the ordering and the selection of the best alternative, multicriteria approach is used in discrete spaces speciffcally the Analytic Hierarchic method, which was developed by Thomas Saaty, by using the software "Hierarchies".
Keywords: C63; 330; simulation; multicriteria; multiattribute; satisfaction